Chronic Stress and Limbic-Hypothalamopituitary-Adrenal Axis (LHPA) Response in Female Reproductive system - Farideh Zafari Zangeneh; Fatemeh Sarmast Shooshtary (Tehran University of Medical Sciences, 2009)
The hypothalamo-pituitary-adrenocortical (HPA) axis is a critical adaptive system that maximizes survival potential in the face of physical or psychological challenge. The principal end products of the HPA axis, glucocorticoid hormones, act on multiple organ systems, including the brain, to maintain homeostatic balance. The brain is a target of stress, and the hippocampus is the first brain region, besides the hypothalamus, to be recognized as a target of glucocorticoids. These anatomical areas in brain are limbic system, and in particular the hippocampus, medial prefrontal cortex (mPFC) and amigdal that have multiple control points in regulation of the hypothalamic-pituitary-adrenal (HPA) axis. The studies show the prefrontal cortex (PFC) plays an important role in the regulation of stress-induced hypothalamic-pituitary-adrenal (HPA) activity and regulation of gonadal function in men and women is under the control of the HPA. This regulation is complex and sex steroids are important regulators of GnRH and gonadotropin release through classic feedback mechanisms in the hypothalamus and pituitary gland. Chronic stress can have a deleterious effect on the reproductive axis that, for females, is manifested in reduced pulsatile gonadotropin secretion and increased incidence of ovulatory abnormalities and infertility. The limbic-hypothalamic-pituitary-adrenal (LHPA) axis suggests a functional role for gonadal steroids in the regulation of a female's response to stress.